2015
DOI: 10.1007/s10238-015-0371-4
|View full text |Cite
|
Sign up to set email alerts
|

β3-tubulin is a good predictor of sensitivity to taxane-based neoadjuvant chemotherapy in primary breast cancer

Abstract: The objective of this study was to explore the relationship between β3-tubulin expression and sensitivity to taxane-based neoadjuvant chemotherapy in primary breast cancer patients. A total of 48 local advanced breast cancer patients that received taxane-containing neoadjuvant chemotherapy were studied. The levels of β3-tubulin expression were tested by immunohistochemistry before chemotherapy and at the end of cycles 2, 4 and 6. The correlation between the efficacy of the chemotherapy and β3-tubulin expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In contrast, free DTX caused similar expression of apoptotic factors, including Bcl-2 and Bax, compared to PBS group, which was consistent with the relatively low therapeutic effect of free DTX. Moreover, multiple doses of DTX–cRGD-Lipep-Ms exhibited also remarkably decreased expression of β 3 tubulin, which is a marker of resistance to docetaxel in many cancers. , In comparison, DTX–Lipep-Ms, though it also led to decreased expression of Bcl-2 and β 3 tubulin, was obviously less effective than DTX–cRGD-Lipep-Ms. These results have shown that DTX–cRGD-Lipep-Ms provide a robust and efficient platform for targeted treatment of α v β 3 receptor-overexpressing malignancies.…”
Section: Resultsmentioning
confidence: 98%
“…In contrast, free DTX caused similar expression of apoptotic factors, including Bcl-2 and Bax, compared to PBS group, which was consistent with the relatively low therapeutic effect of free DTX. Moreover, multiple doses of DTX–cRGD-Lipep-Ms exhibited also remarkably decreased expression of β 3 tubulin, which is a marker of resistance to docetaxel in many cancers. , In comparison, DTX–Lipep-Ms, though it also led to decreased expression of Bcl-2 and β 3 tubulin, was obviously less effective than DTX–cRGD-Lipep-Ms. These results have shown that DTX–cRGD-Lipep-Ms provide a robust and efficient platform for targeted treatment of α v β 3 receptor-overexpressing malignancies.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, it can control the cell cycle and thereby alter cell proliferation, differentiation, and other biological behaviors [6]. According to Xiang et al [16], βIII-tubulin expression changes the features of different endogenous microtubules in tumor cells. These changes cause reduced sensitivity of the binding between the drug and βIII-tubulin dimers.…”
Section: Discussionmentioning
confidence: 99%
“…However, high expression significantly correlated with a higher probability of achieving a good response to chemotherapy. Xiang et al [16] analyzed samples from 48 breast cancer patients who received neoadjuvant therapy containing taxanes. The expression of the βIII-tubulin protein before chemotherapy significantly affects the correlated treatment with the response rate.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 As a component of the TGF-β family, β-tubulin is established as a significant predictor for the efficacy of taxane chemotherapy. 34 Tubulins are also involved in cellular biological events such as microtentacle formation, adhesion, and invasive migration. 35 It is known that tubulins participate in the microtube assembly via its colchicine binding site within the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%